Nationalism and political change in Eastern Europe: the Slovak question and the Czechoslovak reform movement (University of Denver, 1973)
The Sociel Science Foundation and Graduate School of International Studies, University of Denver. Monograph series in world affairs, Editor: Ch.A. Micaud, Vol. 10, monograph 1.